2020
DOI: 10.1002/adma.201908445
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Matrixes for Binder‐Free Nanostructured Electrodes in Lithium‐Ion Batteries

Abstract: Commercial lithium‐ion batteries (LIBs), limited by their insufficient reversible capacity, short cyclability, and high cost, are facing ever‐growing requirements for further increases in power capability, energy density, lifespan, and flexibility. The presence of insulating and electrochemically inactive binders in commercial LIB electrodes causes uneven active material distribution and poor contact of these materials with substrates, reducing battery performance. Thus, nanostructured electrodes with binder‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 294 publications
(1,054 reference statements)
0
113
0
Order By: Relevance
“…What's more, the reserved channels between the cathode materials enable the cathodes to withstand volume changes and enhance their cycling stability. [103] The typical low-tortuous cathode with vertical channels is shown in Figure 8b. VO 2 nanobelt arrays [93] were directly and homogeneously grown on V foil via hydrothermal method evidenced by XRD patterns and SEM image in Figure 8a,b.…”
Section: Promoting Ion Transport Via Vertical Channelsmentioning
confidence: 99%
“…What's more, the reserved channels between the cathode materials enable the cathodes to withstand volume changes and enhance their cycling stability. [103] The typical low-tortuous cathode with vertical channels is shown in Figure 8b. VO 2 nanobelt arrays [93] were directly and homogeneously grown on V foil via hydrothermal method evidenced by XRD patterns and SEM image in Figure 8a,b.…”
Section: Promoting Ion Transport Via Vertical Channelsmentioning
confidence: 99%
“…Hence, it is highly essential to fabricate electrodes without binders to realize enhanced electrochemical properties and robust mechanical flexibility. Binder‐free membrane electrodes thus have stood out over the years [23–26] . The electrodes can completely eliminate the introduction of binders, realize stable electrical contact with conductive matrix, accelerate ion transmission, and improve the gravimetric energy storage capacity of batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, binder-free nanostructured electrodes have been widely investigated considering the advantages of superior mechanical stability, large surface area and high specific capacity. [89] Wang et al [90] reported a facile method to in situ synthesize Bi nanoflakes/Ni foam(Bi/Ni) integrated electrode via replacement reaction, which exhibited attractive cycle performance for SIBs. Liu et al [91] covered each carbon fiber with sexangular bismuth nanosheets to work as advanced binder-free anode for SIBs.…”
Section: Metallic Bi and Its Compositesmentioning
confidence: 99%